MEMS resonator filters - Patrikar, Rajendra M. (Materials, circuits and devices series, 2020)
This book explores the challenges and opportunities of developing circuits with MEMS resonator filters. The replacement of classical electrical components with electromechanical components is explored in this book, and the specific properties of MEMS resonators required in various frequency ranges are discussed.